Vulnerability to climate change: Evidence from a dynamic factor model - Haroon Mumtaz; Fulvia Marotta (Queen Mary University of London, School of Economics and Finance, 2023)
Using a dynamic factor model with stochastic volatility, we examine the synchronization of temperature and precipitation changes across countries and regions. By doing so, we analyze the implications for the medium-term economic outlook and vulnerability to climate risks. Our findings reveal that a common factor explains a significant portion of temperature variance globally, with the largest contribution observed in sub-Saharan Africa, Latin America, and Asia. Additionally, the common factor accounts for the increase in temperature levels across these regions. In contrast, precipitation fluctuations exhibit more localized patterns. We find that countries with higher GDP per-capita tend to have lower exposure to global temperature changes.
Keywords: 330; Climate change; Temperatures; Economic vulnerability; Dynamic factor model